Enhancing mechanical properties of 2024-Aluminium Alloy Matrix Composite strengthened by Y2O3 ceramic particles - Mhmood Salim Hassoon; İsmail H. Kara; Ahmed H. Ali; Hamid M. Mahan, (International Journal of Nanoelectronics and Materials (IJNeaM), 2024)
The development of high-strength, low-weight composite materials has been a high-priority demand in the structural, aerospace, automotive, renewable energy, and sports equipment sectors. Micro-particle size Yttrium oxide (Y2O3) has been utilized to enhance the microstructure and mechanical characteristics of the 2024-Al alloy. The stir-casting technique is employed to prepare 2024-Al alloy and aluminum matrix composites (AMCs) with different Y2O3 weight fractions (1 %, 2 %, and 3 %). Scanning electron microscope ESM with EDS analysis and optical microscope imaging have been used to assess the development in the microstructure of AMCs. Furthermore, optical microscope images have been analyzed by using image processing software, ImageJ to evaluate development in microstructure grain size. Vickers' micro-hardness, tensile strength, elongation, and wear-resistant tests were conducted to assess the mechanical properties of AMCs. AMC image analysis results demonstrated a significant reduction in microstructure grain size. The highest reduction in grain size was recorded when adding 2 wt. % of Y2O3, which was approximately 22.5 % smaller than that of the plain alloy. Other mechanical test results demonstrated an increase in the hardness and tensile strength of AMCs compared with the plain alloy by approximately 58 % and 116 %, respectively, upon the addition of 2 wt. % of Y2O3, also tensile test shows increasing of AMCs elongation at failure point with increasing Y2O3 content, 132 % upon adding 3 wt. %. Finally, wear tests show a decrease in the AMC wear rate with an increasing Y2O3 weight fraction compared to the plain alloy.